STRATEGIES FOR ECONOMIC GROWTH AND DEVELOPMENT IN THE GLOBAL ERA BASED ON CICIV ECONOMC EDUCATION - Bintang, Abraham; Dinata, Rafael Putra (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
The study of this study aims to determine the strategy of growth and development of the economy in the global era based on citizenship economic education. This research is conceptual research using the Library Research method, which is collecting data from scientific articles, research reports or other things that are relevant to the topic. The results of the analysis show that economic growth and development in the global era can be integrated through the concept of citizenship economic education in the community and school environment in the form of entrepreneur programs, business unit development, improving the quality of human resources, and the use of technology and information.